Creativity : When East Meets West. - Lau, Sing (World Scientific, 2004)
What actually is creativity? And what contributes to itsconceptualization and development? For decades, these and otherquestions have fascinated researchers, educators, parents andlaypeople alike, and equally so in the East and West. This interestingcollection of articles is an attempt at exploring and answering theabove questions from both the Eastern and Westernperspectives. Readers may find some answers stimulating, and othersbewildering. This is in fact the reality and fascination of.